1996
DOI: 10.1074/jbc.271.26.15358
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional Reconstitution into Detergent-destabilized Liposomes of the Purified Lactose Transport System of

Abstract: The lactose transport protein (LacS) of Streptococcus thermophilus was amplified to levels as high as 8 and 30% of total membrane protein in Escherichia coli and S. thermophilus, respectively. In both organisms the protein was functional and the expression levels were highest with the streptococcal lacS promoter. Also a LacS deletion mutant, lacking the carboxyl-terminal regulatory domain, could be amplified to levels >20% of membrane protein. Membranes from S. thermophilus proved to be superior in terms of ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
150
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(155 citation statements)
references
References 35 publications
5
150
0
Order By: Relevance
“…Although previous characterization of phosphate transport activity of the purified protein was accomplished by reconstitution into liposomes with the same lipid composition as used in this work, the driving force for Pho84-catalyzed phosphate accumulation was provided by an artificial pH gradient (interior alkaline). Reconstitution of Pho84 into liposomes composed of E. coli phospholipids and egg phosphatidylcholine as previously described for reconstitution of lactose transporter of St. thermophilus (13) and prepared according to the procedure described by Berhe et al (10) resulted in an inactive membrane-bound Pho84 permease. In the study presented here, we have shown that purified cytochome c oxidase from beef heart can be functionally reconstituted into artificial lipid membranes with the lipid composition previously successfully employed for coreconstitution of purified nicotinamide nucleotide transhydrogenase and ATPase from beef heart mitochondria (26), purified beef heart nicotinamide nucleotide transhydrogenase and bacteriorhodopsin from Halobacterium halobium (27), and the Pho84 phosphate permease of S. cereVisiae (10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although previous characterization of phosphate transport activity of the purified protein was accomplished by reconstitution into liposomes with the same lipid composition as used in this work, the driving force for Pho84-catalyzed phosphate accumulation was provided by an artificial pH gradient (interior alkaline). Reconstitution of Pho84 into liposomes composed of E. coli phospholipids and egg phosphatidylcholine as previously described for reconstitution of lactose transporter of St. thermophilus (13) and prepared according to the procedure described by Berhe et al (10) resulted in an inactive membrane-bound Pho84 permease. In the study presented here, we have shown that purified cytochome c oxidase from beef heart can be functionally reconstituted into artificial lipid membranes with the lipid composition previously successfully employed for coreconstitution of purified nicotinamide nucleotide transhydrogenase and ATPase from beef heart mitochondria (26), purified beef heart nicotinamide nucleotide transhydrogenase and bacteriorhodopsin from Halobacterium halobium (27), and the Pho84 phosphate permease of S. cereVisiae (10).…”
Section: Discussionmentioning
confidence: 99%
“…The appropriate amounts of lipids were dried under N 2 (g), redissolved in diethyl ether, washed with ethanol, dried, resuspended to a final concentration of 20 mg/mL in 25 mM K + /Hepes (pH 7.0) and 0.1% Triton X-100, sonicated to clarity, and mixed with purified Pho84 protein at a concentration of 0.14 mg/mL. The protein/lipid mixture was incubated for 30 min at 4°C, after which the detergent was removed by a sequential Biobeads treatment essentially according to the method of Knol et al (13). Fresh Biobeads (80 mg/mL of liposome mixture), extensively washed with methanol and ethanol and finally rinsed in water, were added and incubated at 4°C under slow agitation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of SEC-LS for three membrane proteins will be given: the glutamate transporter GltT [16], the lactose transporter LacS [17] and the riboflavin transporter RibU [18]. Other examples can be found in references [2,3,7,[19][20][21][22].…”
Section: How Do Membrane Proteins Behave In the Sec-ls Analysis?mentioning
confidence: 99%
“…Histidine tagged LacS (A 280 = 1.01 ml mg À1 cm À1 ), GltT (A 280 = 0.62 ml mg À1 cm À1 ) and RibU (A 445 = 0.45 ml mg À1 cm À1 ) were purified as described using Ni-affinity chromatography [16][17][18]. The proteins were further purified using size exclusion chromatography in SEC buffer (20 mM Tris/HCl, pH 7.5, 150 mM NaCl, 0.04% DDM, filtered through 0.1 lm pore size VVLP filters (Millipore)) as described for RibU [18].…”
Section: Protein Preparationmentioning
confidence: 99%